Development of Android-Based Interactive Media KaLoT on Cultural Diversity and Local Wisdom - Arin Eko Yulianto; Rahyu Setiani; Ajar Dirgantoro; Dian Septi Nur Afifah (SAGA: Journal of Technology and Information System, 2025)
The availability of interactive learning media determines the success of educational processes, especially in implementing the Merdeka Curriculum. This study was motivated by low learning interest (mean 53.9%) and IPAS learning outcomes (mean 68.5; below the KKTP of 75) among fourth-grade students at SD Negeri 1 Nglebo, Trenggalek, attributable to limited instructional media. This study developed the Android-based interactive learning application "KaLoT" (Keragaman Budaya memuat Kearifan Lokal Trenggalek), integrating national cultural diversity with Trenggalek local wisdom. The Research and Development (R&D) methodology with the ADDIE model was employed, involving 14 students (SD Negeri 2 Suruh) for small-group trials and 23 students (SD Negeri 1 Nglebo) for large-group trials. Data were collected via expert validation sheets, teacher response questionnaires, classroom observation sheets, learning interest questionnaires, and HOTS-based pre-test/post-test assessments, analyzed using quantitative descriptive analysis and N-Gain. Results demonstrated: (1) very high validity at 93.85%; (2) very high practicality averaging 93.46%; and (3) effective improvement of learning outcomes with N-Gain of 0.71 (small group), 0.75 (Class IVA), and 0.66 (Class IVB), with learning interest rising from 53.5–55.8% to 91.0–93.2%. The study concludes that "KaLoT" is valid, practical, and effective for IPAS learning in Grade IV elementary school.